Early growth and fruit development of fig (ficus carica L.) - Muhammad Syufihuddin Shamsuddin (Kulliyyah of Science, International Islamic University Malaysia, 2020)
Fig (Ficus carica L.) is a member of family Moraceae that originated from the Mediterranean region. Fig is widely planted for its fruit which can be eaten fresh and dried. The demand for fig seedlings is currently on the rise amongst Malaysians, but the main problem is that there is insufficient production of fig seedlings as a result of low production scales. Propagation using stem cutting can be used as this method can contribute to large-scale production. However, there is a lack of knowledge on agronomic practices related to the propagation of stem cutting in Malaysia. Besides, fig fruit is usually imported from other countries however it can be produced in Malaysia. However, there is still no information on fig fruit production in Malaysia. This experiment aims to study the effect of different planting medium and cutting type on an early shoot and root development of Ficus carica and also the development of the fruit of Ficus carica as affected by the different rates of chicken manure. The first study emphasizes the effect of planting medium and type of stem cutting on the early growth of the shoot and root system of F. carica. The research was conducted in the glasshouse at the Glasshouse and Nursery Complex (GNC), International Islamic University Malaysia (IIUM) Kuantan Campus. Three kinds of media combinations of topsoil, sand, sawdust, peat, and perlite were used as planting medium. Meanwhile, two kinds of stem cuttings which were semi-hardwood and hardwood were used as cutting material. The experiment was conducted with five replications in a split-plot design. Data on the shoot and root systems were recorded and analyzed through analysis of variance (ANOVA). The root anatomical structure was prepared through a series of histological work. Samples were observed and analyzed using Leica LAS EZ software. Results showed that 50% peat and 50% perlites give the highest performance on the early growth of the shoot and root of F. carica. Thus, it is recommended to use the mixture of 50% peat: 50% perlite and hardwood stem cuttings as planting medium and type of cutting for early fig growth. The second study was on the growth performance of fruit affected by different rates of chicken manure. This study was conducted in the open area of the GNC, IIUM Kuantan Campus. The experiment was arranged in a randomized completely block design (RCBD) of six blocks. Four rates of chicken manure used were 0 g chicken manure (T1), 150 g chicken manure, 300 g chicken manure, and 450 g chicken manure. Data on fruit development were recorded and analyzed through analysis of variance (ANOVA) by using open software SAS. The result showed that the application of 450 g chicken manure (T4) produces the highest fruit performance compared to all treatments. Thus, it showed that a higher amount of organic fertilizer used significantly increase the fruit performance of F. carica.